Putting Behavioral Goal-Setting Research Into Practice. (August 2017) - Bruhn, Allison Leigh; Fernando, Josephine; McDaniel, Sara; Troughton, Leonard
Students with or at risk of emotional and behavioral disorders can benefit from a variety of self-regulation strategies. One such strategy is goal setting, which can be used to improve both academic and behavioral outcomes in the classroom. In this article, we discuss the importance of goal setting and current research in this area. In addition, we provide a step-by-step process for implementing goal-setting interventions in the classroom.